Implementation of the Role of BPN in the Conversion of Cultivated Land of Indigenous Law Communities from the Perspective of Land Law - Mulya, Winda Hasna (Universitas Islam Negeri Sumatera Utara, 2026)
The conversion of land cultivated by indigenous legal communities has become an increasingly complex agrarian issue in Indonesia amid the expansion of development and investment. For indigenous communities, land is not merely an economic asset but also carries social, cultural, and spiritual values as part of their collective identity. This study explicitly aims to analyze the implementation of the role of the National Land Agency (Badan Pertanahan Nasional/BPN) in land conversion involving indigenous legal communities and to assess its legal responsibility in providing legal certainty and protection of land rights from a land law perspective. This research is significant because previous studies have mainly focused on agrarian conflicts or normative recognition of customary land rights, while limited attention has been given to examining BPN’s institutional role in the practical implementation of land conversion affecting indigenous communities. This study employs a normative juridical method using statutory, conceptual, and case approaches, particularly analyzing Supreme Court Decision No. 3380 K/Pdt/2020, supported by primary and secondary legal materials. The analysis is conducted qualitatively using deductive legal reasoning. The findings reveal that BPN’s role remains predominantly administrative and has not yet optimally fulfilled its protective function toward indigenous land rights. Therefore, strengthening BPN’s substantive and participatory role is essential to ensure that land conversion policies align with the principles of agrarian justice.